Isolation of nontuberculous mycobacteria species from different water sources: a study of six hospitals in Tehran, Iran - Sina Moghaddam; Farshad Nojoomi; Arasb Dabbagh Moghaddam; Mojgan Mohammadimehr; Fatemeh Sakhaee; Morteza Masoumi; Seyed Davar Siadat; Abolfazl Fateh (BMC Microbiology, 2022)
Abstract Purpose Nontuberculous mycobacteria (NTM) are ubiquitous bacteria that are naturally resistant to disinfectants and antibiotics and can colonize systems for supplying drinking water. Therefore, this study aimed to evaluate the prevalence of NTM in the drinking water of six hospitals in Tehran, Iran. Methods Totally, 198 water samples were collected. Each water sample was filtered via a membrane filter with a pore size of 0.45 µm and then decontaminated by 0.005% cetylpyridinium chloride. The membrane filters were incubated on two Lowenstein-Jensen media at 25 °C and 37 °C for 8 weeks. The positive cultures were identified with phenotypic tests, and then NTM species were detected according to the hsp65, rpoB, and 16S rDNA genes. Drug susceptibility testing (DST) was also carried out. Results Overall, 76 (40.4%) of the isolates were slowly growing mycobacteria (SGM) and 112 (59.6%) of the ones were rapidly growing mycobacteria (RGM). The most common NTM were Mycobacterium aurum, M. gordonae, M. phocaicum, M. mucogenicum, M. kansasii, M. simiae, M. gadium, M. lentiflavum, M. fortuitum, and M. porcinum. Among these 188 samples, NTM ranged from 1 to > 300 colony-forming unit (CFU) /500 mL, with a median of 182 CFU/500 mL. In the infectious department of all hospitals, the amount of CFU was higher than in other parts of the hospitals. The DST findings in this study indicated the diversity of resistance to different drugs. Among RGM, M. mucogenicum was the most susceptible isolate; however, M. fortuitum showed a different resistance pattern. Also, among SGM isolates, M. kansasii and M. simiae, the diversity of DST indicated. Conclusions The current study showed NTM strains could be an important component of hospital water supplies and a possible source of nosocomial infections according to the CFU reported in this study. The obtained findings also help clarify the dynamics of NTM variety and distribution in the water systems of hospitals in the research area.